21 Окт 2021 в 19:41
26 +1
0
Ответы
1

To solve this equation, we need to use the properties of logarithms.

First, we can combine the two logarithmic terms on the left side of the equation using the quotient rule of logarithms. This rule states that log_a(b) - log_a(c) = log_a(b/c).

So, we have:

log_7((2x^2 - 7x + 6)/(x - 2)) = log_7(x)

Now, we can remove the logarithms by exponentiating both sides with base 7.

This gives us:

(2x^2 - 7x + 6)/(x - 2) = x

Now, we can simplify this equation by multiplying both sides by (x - 2) to get rid of the fraction:

2x^2 - 7x + 6 = x(x - 2)
2x^2 - 7x + 6 = x^2 - 2x

Next, we can combine like terms and set the equation equal to zero:

x^2 - 5x + 6 = 0

Now, we can factor this quadratic equation:

(x - 2)(x - 3) = 0

Setting each factor equal to zero gives us the solutions:

x - 2 = 0 or x - 3 = 0

Therefore, the solutions to the original equation are x = 2 or x = 3.

17 Апр в 09:40
Не можешь разобраться в этой теме?
Обратись за помощью к экспертам
Название заказа не должно быть пустым
Введите email
Бесплатные доработки
Гарантированные бесплатные доработки
Быстрое выполнение
Быстрое выполнение от 2 часов
Проверка работы
Проверка работы на плагиат
Интересные статьи из справочника
Поможем написать учебную работу
Название заказа не должно быть пустым
Введите email
Доверьте свою работу экспертам
Разместите заказ
Наша система отправит ваш заказ на оценку 91 633 авторам
Первые отклики появятся уже в течение 10 минут
Прямой эфир